Mechanical properties of built-up timber beams with various cross sections determined using analytical methods. Issue 2 (4th March 2023) - Tsai, Meng-Ting; Le, Truong-Di-Ha; Chang, Feng-Cheng
ABSTRACT: In this study, analytical methods were used to investigate the performance of built-up timber (BT) beams with different designs. A simplified analytical approach based on the gamma and capacity methods was used to evaluate the initial stiffness, allowable strength, and ultimate strength of BT beams. Current analytical methods cannot be used to estimate the ductility ratio, thus hampering the development of a complete analytical model for BT beams. In this study, a complete analytical model was established for BT beams. In this model, the ductility ratio is determined according to experimental results. The ductility ratios of specimens were determined using the equivalent energy method. The developed complete analytical model for BT beams can accurately model the behavior of these beams. The estimated ductility ratios suggest that specimens with one web and two webs are suitably ductile and marginally brittle, respectively. The developed model can be used to predict the flexural performance of BT beams with different design parameters, and the ductility ratio can be applied in structural design.